2017
DOI: 10.1007/s10641-017-0706-y
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of the tiger shark, Galeocerdo cuvier, in the northwest Atlantic Ocean and Gulf of Mexico

Abstract: Sharks are apex predators that structure marine communities through predation. Studies of diet and feeding patterns contribute to developing ecosystem models and it is critical that whenever possible, diet information specific to the area of concern is applied when developing an ecosystem model. Despite a number of studies conducted on tiger shark feeding, most comprehensive studies have been from the Pacific Ocean. There is little knowledge of the diet of tiger sharks in the Atlantic Ocean and Gulf of Mexico,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…Comparison of the diet between large and small tiger sharks within the GMR revealed an ontogenetic shift, with small tiger sharks generally feeding on lower trophic groups. Pelagic fish and squid were the main prey items, similarly to other trophic studies in sub-adult individuals along the coast of Ecuador [22], Western Australia [17] and the north-western Atlantic [21]. Ontogenetic dietary shifts, in which the number and size of prey items increase as tiger sharks increase in size, have also been reported around Hawaii [13], New Caledonia [11], and South Africa [20].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Comparison of the diet between large and small tiger sharks within the GMR revealed an ontogenetic shift, with small tiger sharks generally feeding on lower trophic groups. Pelagic fish and squid were the main prey items, similarly to other trophic studies in sub-adult individuals along the coast of Ecuador [22], Western Australia [17] and the north-western Atlantic [21]. Ontogenetic dietary shifts, in which the number and size of prey items increase as tiger sharks increase in size, have also been reported around Hawaii [13], New Caledonia [11], and South Africa [20].…”
Section: Discussionsupporting
confidence: 56%
“…In the northwestern Hawaiian Islands, seabirds are the most important prey items [18]; while tiger sharks around the main Hawaiian islands display a broader diet composition [13,19]. A limited number of studies are available from other geographical areas, such as the Indian [20], Atlantic [21] or Eastern Pacific [22] ocean basins. In the Tropical Eastern Pacific, diet studies for this species have been limited to the analysis of stomach contents from just six individuals from the coast of mainland Ecuador [22].…”
Section: Introductionmentioning
confidence: 99%
“…A more likely explanation for lower transmission rates at smaller sizes is behavioral, namely that smaller animals simply spend less time at the surface than larger individuals. Younger individuals in the GoM are reported to forage disproportionately on benthic gastropods [83], whereas adults, which are known to spend the majority of their time at depths <5 m [48,84], more commonly consume sea turtles and fishes [83]. Additionally, smaller individual tiger sharks are likely more susceptible to predation from larger sharks and as such may avoid these areas at younger life stages to improve survival.…”
Section: Study Limitations and Recommendationsmentioning
confidence: 99%
“…Several species of sharks prey on sea snakes (Heatwole et al, 1974;Tuma, 1976;Lyle, 1987;Cliff and Dudley, 1991;Simpfendorfer, 1992;Lowe et al, 1996;Fergusson et al, 2000;Heithaus, 2001;Kerford, 2005). Notably, tiger sharks are important in this respect (Dicken et al, 2017;Ferreira et al, 2017;Aines et al, 2018; Figure 6). In coastal waters of Queensland, Australia, Heatwole (1974) found that 31% of the 637 tiger sharks that contained food had at least one sea snake in their stomachs.…”
Section: Lethal Effects Of Increased Predator Abundancementioning
confidence: 99%